Abnormalities of growth hormone release in response to human pancreatic growth hormone releasing factor (GRF (1-44) ) in acromegaly and hypopituitarism. Issue 6379 (28th May 1983) - Wood, S M; Ch'ng, J L; Adams, E F; Webster, J D; Joplin, G F; Mashiter, K; Bloom, S R
Abstract : Human pancreatic growth hormone releasing factor (GRF (1-44)) is the parent molecule of several peptides recently extracted from pancreatic tumours associated with acromegaly. A study was conducted to examine its effects on the release of growth hormone in normal volunteers and in patients with hypopituitarism and acromegaly. GRF (1-44) dose dependently stimulated the release of growth hormone in normal people and produced no appreciable side effect. This response was grossly impaired in patients with hypopituitarism and, although similar to the growth hormone response to hypoglycaemia, was of quicker onset and a more sensitive test of residual growth hormone function. Patients with acromegaly appeared to fall into (a) those with a normal response to GRF, whose growth hormone suppressed significantly with oral glucose, and (b) those who had an exaggerated response to GRF (1-44), whose growth hormone had not suppressed previously after oral glucose. Present methods for testing growth hormone deficiency entail using the insulin stress test, which is time consuming, unpleasant, and sometimes dangerous. A single intravenous injection of GRF now offers the possibility of an easier, safer, and more reliable routine test for growth hormone deficiency. It has the further advantage of being free of side effects and readily performed in outpatients. Hence it seems likely to become the standard test and take the place of the insulin stress test.